Defense against outside competition is linked to cooperation in male-male partnerships - Hellmann, Jennifer K.; Stiver, Kelly A.; Marsh-Rollo, Susan; Alonzo, Suzanne H. (Behavioral Ecology, 2020)
Male–male competition is a well-known driver of reproductive success and sexually selected traits in many species. However, in some species, males work together to court females or defend territories against male competitors. Dominant (nesting) males sire most offspring, but subordinate (satellite) males are better able to obtain fertilizations relative to unpartnered males. Because satellites only gain reproductive success by sneaking, there has been much interest in identifying the mechanisms enforcing satellite cooperation (defense) and reducing satellite sneaking. One such potential mechanism is outside competition: unpartnered satellites can destabilize established male partnerships and may force partnered satellites to restrain from cheating to prevent the dominant male from replacing them with an unpartnered satellite. Here, we manipulated perceived competition in the Mediterranean fish Symphodus ocellatus by presenting an “intruding” satellite male to established nesting and satellite male pairs. Focal satellite aggression to the intruder was higher when focal satellites were less cooperative, suggesting that satellites increase aggression to outside competitors when their social position is less stable. In contrast, nesting male aggression to the intruder satellite increased as spawning activity increased, suggesting that nesting males increase their defense toward outside competitors when their current relationship is productive. We found no evidence of altered spawning activity or nesting/satellite male interactions before and after the presentation. These results collectively suggest that response to outside competition is directly linked to behavioral dynamics between unrelated male partners and may be linked to conflict and cooperation in ways that are similar to group-living species.
Keywords: Satellites; Symphodus ocellatus; alternative reproductive tactics; biological market theory; cooperation; cooperative behavior; defense mechanism; dept.psy; interspecific competition; intraspecific interaction; outside options; peer-reviewed; satellite male; sneak